Stomata at the crossroad of molecular interaction between biotic and abiotic stress responses in plants - Peng, Pengshuai; Li, Rui; Chen, Zhong-Hua; Wang, Yuanyuan (Frontiers in Plant Science, 2022)
Increasing global food production is threatened by harsh environmental conditions along with biotic stresses, requiring massive new research into integrated stress resistance in plants. Stomata play a pivotal role in response to many biotic and abiotic stresses, but their orchestrated interactions at the molecular, physiological, and biochemical levels were less investigated. Here, we reviewed the influence of drought, pathogen, and insect herbivory on stomata to provide a comprehensive overview in the context of stomatal regulation. We also summarized the molecular mechanisms of stomatal response triggered by these stresses. To further investigate the effect of stomata–herbivore interaction at a transcriptional level, integrated transcriptome studies from different plant species attacked by different pests revealed evidence of the crosstalk between abiotic and biotic stress. Comprehensive understanding of the involvement of stomata in some plant–herbivore interactions may be an essential step towards herbivores’ manipulation of plants, which provides insights for the development of integrated pest management strategies. Moreover, we proposed that stomata can function as important modulators of plant response to stress combination, representing an exciting frontier of plant science with a broad and precise view of plant biotic interactions.